(untitled) (Research, Society and Development, 2020)
At the end of 2019, a new virus emerged in Wuhan, China, there was an unrestrained spread in several countries, until the World Health Organization declared a pandemic state, and the changes that are causing it all over the world have been the subject of constant concern. by health professionals. Coronavirus mortality has already reached more than 4%, and although there are numerous researches in progress, trials based on the hypothesis of vaccine formulation, there is still no effective and safe treatment, patients with COVID-19 have an inflammatory state especially in interleukins. It is an integrative review, based on the publications contained in the PUBMED and SCIELO.ORG databases, with articles in the timeline of the first 5 months of the year 2020, all articles were found using the combinations of the following descriptors arranged in DECs: COVID-19, infections, Vitamin D, infection and Vitamin D, in English, Portuguese and Spanish. Several studies point to the actions of vitamin D in reducing inflammatory microbial activities, and it helps to increase immunity by decreasing cytokine activity. Vitamin D deficiency has been identified as one of the protective factors for the risk of COVID-19, since the receptors for this vitamin are widely distributed in the respiratory tract, since vitamin D activation is driven by stimulation processes, Adequate concentrations of 25 (OH) D is important to avoid complications and viral replications in the body.